Production of low-silicon molten iron from high-silica hematite using biochar - Tang, Hui-qing; Fu, Xiu-feng; Qin, Yan-qi; Zhao, Shi-yu; Xue, Qing-guo (Journal of iron and steel research, international, 2017)
A new method of utilizing high-silica hematite to produce low-silicon molten iron was proposed.In this method,FASTMELT,which comprised direct reduction and melt separation processes,was applied,with highly reactive biochar as the reductant in the direct reduction stage.The proposed method was experimentally investigated and the results show that the method is feasible.In the direct reduction stage,ore-char briquette could achieve a metallization rate of 84%-88% and residual carbon of 0.27-0.89mass% at temperature of 1373 K,biochar mixing ratio of 0.8-0.9,and reduction time of 15 min.Some silica particles remained embedded in the iron phase after the reduction.In the melting separation stage,molten iron with a carbon content of 0.02-0.03mass% and silicon content of 0.02-0.18mass%could be obtained from the metallic briquettes under the above-mentioned conditions;the iron recovery rate was83%-91% and impurities in the obtained metal were negligible.